О происхождении частицы ku в армянском языке - Геворкян, Гаянэ (Институт языкознания РАН)
The grammatical particle կու/ku appears for the first time in written sources at the beginning of the 12th century. Initially limited in use, it spread widely in the following centuries. Regional differences in pronunciation of կու/ku suggest its transformation due to broad use. When considering the origin of կու/ku, it is necessary to take into account that in the regional dialects of Armenian the current particles could not have developed from one form only. Based on pronunciation, not only the transition of կոյ/koy – կու/ku is justifiable, but also that of կոյ / koy – կի / ki.
Keywords: Армянский язык; Языкознание; Язык, письмо